1999
DOI: 10.1086/314727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Intermittent Administration of Inhaled Tobramycin on Respiratory Microbial Flora in Patients with Cystic Fibrosis

Abstract: Pseudomonas aeruginosa endobronchial infection causes significant morbidity and mortality among cystic fibrosis patients. Microbiology results from two multicenter, double-blind, placebo-controlled trials of inhaled tobramycin in cystic fibrosis were monitored for longitudinal changes in sputum microbial flora, antibiotic susceptibility, and selection of P. aeruginosa isolates with decreased tobramycin susceptibility. Clinical response was examined to determine whether current susceptibility standards are appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
3
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(163 citation statements)
references
References 19 publications
(20 reference statements)
6
148
3
6
Order By: Relevance
“…81 Although previous works detected no association between ABPA and P. aeruginosa colonisation. 82 Nikolaizik et al reported a positive correlation between the two entities, suggesting that P. aeruginosa colonisation favours the process of A. fumigatus sensitisation.…”
Section: Abpamentioning
confidence: 90%
“…81 Although previous works detected no association between ABPA and P. aeruginosa colonisation. 82 Nikolaizik et al reported a positive correlation between the two entities, suggesting that P. aeruginosa colonisation favours the process of A. fumigatus sensitisation.…”
Section: Abpamentioning
confidence: 90%
“…Resistanceconferring mutations do occur, probably selected for by intensive antibiotic treatments. However, isolates of P. aeruginosa strains do not always develop resistance (Burns et al, 1999;Gibson et al, 2003;Gilligan, 2006;Mulcahy et al, 2010). Lewis (2007) suggested that the recalcitrant nature of P. aeruginosa infections in CF lungs is largely the consequence of the presence of a drug-tolerant subpopulation of persister cells.…”
Section: Cystic Fibrosis Pneumoniamentioning
confidence: 99%
“…Expectorated sputum samples were cultured quantitatively and throat swabs were cultured semi-quantitatively on selective media, as previously reported. 20 Minimal inhibitory concentrations (MIC) of aztreonam were determined for all P. aeruginosa isolates using a semiautomated broth microdilution technique (Sensititre, Trek Diagnostic Systems, Cleveland, OH) according to Clinical Laboratory and Standards Institute (CLSI) standards. MIC testing was performed on each distinctive P. aeruginosa morphotype isolated from an individual sample.…”
Section: Microbiologymentioning
confidence: 99%